Transforming Customer Loyalty: The Synergy of Experience, Corporate Image, and Digital Marketing at BPRS Dana Amanah Surakarta - Ananda Rizki Akbar; Sokhikhatul Mawadah; Ahmad Furqon (AL-ARBAH: Journal of Islamic Finance and Banking, 2026)
Purpose - This study aims   to determine the effect of customer experience variables, company image, and digital marketing on customer loyalty. Method - This research uses quantitative research methods. The data used is primary data with a sample of 100 samples. Sampling is done by accidental sampling technique which is a sampling technique based on coincidence and availability if the sample encountered is suitable as a data source. Result - The results of this study indicate that customer experience variables, company image, and digital marketing have a significant positive effect on customer loyalty. Implication - This study examines the influence of customer experience variables, company image, and digital marketing on customer loyalty at BPRS Dana Amanah Surakarta. Originality - These findings provide a basis for BPRS Dana Amanah Surakarta to always pay attention to service excellence to customers because it will affect the experience when transacting, maintaining the image of BPRS Dana Amanah. Keywords: Customer Experience, Corporate Image, Digital Marketing, and Customer Loyalty